2013
DOI: 10.1111/jpy.12129
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine effects on protein disulfide isomerase expression and implications for hypersalinity stress in the marine algaUlva lactucaLinnaeus1

Abstract: Full-length protein disulfide isomerase (UfPDI) cDNA was cloned from the intertidal macroalga Ulva lactuca Linnaeus. Modulation of UfPDI expression by stresses and polyamines (PA) was studied. UfPDI transcription and enzyme activity were increased by hypersalinity (90) or high light illumination (1,200 μmol photons · m(-2)  · s(-1) ), decreased by the addition of 100 μM CuSO4 . An exposure to a salinity of 90 decreased PA contents. Treating with PA biosynthetic inhibitors, D-arginine (D-Arg) or α-methyl ornith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Chen et al [ 74 ] reported that the heterologous expression of a PDI-like protein from Methanothermobacter thermoautotrophicum protected protein synthesis, increased protein stability, and enhanced Hg tolerance in rice. Exposure to a lower concentration of CuSO 4 (< 20 μM) did not affect the expression of PDI in the marine alga Ulva lactuca , but exposure to a higher level significantly decreased the PDI transcription level [ 75 ]. In Cucumis sativus roots, one PDI was up-regulated under Fe deficiency, while another was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 74 ] reported that the heterologous expression of a PDI-like protein from Methanothermobacter thermoautotrophicum protected protein synthesis, increased protein stability, and enhanced Hg tolerance in rice. Exposure to a lower concentration of CuSO 4 (< 20 μM) did not affect the expression of PDI in the marine alga Ulva lactuca , but exposure to a higher level significantly decreased the PDI transcription level [ 75 ]. In Cucumis sativus roots, one PDI was up-regulated under Fe deficiency, while another was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to higher plants relatively little is known about the role of PAs in algae, although Put, Spd and Spm, as well as some less common PAs, have been detected in macroalgae. Further, Li et al (2013) noticed the induction of protein disulphide isomerase (UfPDI) by hypersalinity in U. lactuca and reported that UfPDI expression get induced by Spd or Spm in contrast to Put before exposure to hypersaline conditions and continued up-regulated after hypersalinity exposure contributing to salinity tolerance and restoring the growth rate. Endogenous and/or exogenous PAs have been shown to modulate stress triggered ROS homeostasis and oxidative damage (mediated by molandialdehyde1) by enhancing the antioxidant enzyme activities including SOD, CAT, APX and GR and pools of nonenzymatic antioxidants (Kumar et al, , 2010.…”
Section: Involvements Of Pas Proline Mycosporine-like Amino Acid Dmentioning
confidence: 99%
“…These secondary metabolites have been analysed in marine plants using a targeted metabolite approach with a RP-HPLC based system coupled with fluorescence detection after derivatization of plant crude extract with either dansylchloride or benzoylchloride [36,123]. In marine plants, the function of PAs has been examined in cell division, maturation of reproductive structures and callus induction [124]; however, their function as stress alleviators against salinity, desiccation stress and metal toxicity has only recently been recognized [34][35][36]123,[125][126][127][128]. For example, a hyposaline shock to Grateloupia turuturu has been shown to accumulate free Put, Spd and Spm together with a significant decrease in transglutaminase activity and an increase in arginine-dependent PA synthesis [125].…”
mentioning
confidence: 99%
“…For example, a hyposaline shock to Grateloupia turuturu has been shown to accumulate free Put, Spd and Spm together with a significant decrease in transglutaminase activity and an increase in arginine-dependent PA synthesis [125]. Furthermore, pre-treatment of Ulva lactuca with Spd or Spm, in contrast to Put, resulted in constantly higher expression of protein disulphide isomerase (UfPDI) when exposed to hypersalinity, suggesting the potential of PAs to alleviate salinity stress and restore the growth rate [127]. Further, the elevated expression of methionine adenosyltransferase (MAT; catalyses spermine synthesis from methionine) in Undaria pinnatifida under hypersalinity and desiccation stress further suggested the role of PAs as stress alleviators [129].…”
mentioning
confidence: 99%